The Influence of Operating Cash Flow, Liquidity, and Financial Leverage on Profitability in Listed Food and Beverage Firms in Indonesia (2021–2024) - Rabiev, Hasan; Hakim, Heikal Muhammad Zakaria (Peneliti.net, 2025)
This study examines the influence of operating cash flow (OCF), liquidity (current ratio), and financial leverage (debt-to-equity ratio) on the profitability of food and beverage firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The research employs a quantitative methodology and multiple linear regression analysis on a sample of seven enterprises, demonstrating that liquidity strongly influences profitability, although operating cash flow and financial leverage exhibit no notable individual effect. The results underscore the essential importance of sustaining adequate liquidity in post-pandemic financial administration. This study provides empirical evidence to enhance financial decision-making and investment assessment in the Indonesian food and beverage sector.